Robotic single-site supracervical hysterectomy with manual morcellation: Preliminary experience - Ding, Dah-Ching (World J Clin Cases, 2017)
AIM: To evaluate the feasibility, safety and peri- and postoperative outcomes of robotic single-site supracervical hysterectomy (RSSSH) for benign gynecologic disease. METHODS: We report 3 patients who received RSSSH for adenomyosis of the uterus from November 2015 to April 2016. We evaluated the feasibility, safety and outcomes among these patients. RESULTS: The mean surgical time was 244 min and the estimated blood loss was 216 mL, with no blood transfusion necessitated. The docking time was shortened gradually from 30 to 10 min. We spent 148 min on console operation. Manual morcellation time was also short, ranging from 5 to 10 min. The mean hospital stay was 5 d. Lower VAS pain score was also noted. There is no complication during or after surgery. CONCLUSION: RSSSH is feasible and safe, incurs less postoperative pain and gives good cosmetic appearance. The technique of in-bag, manual morcellation can avoid tumor dissemination.